Wayang in the Classroom: Punakawan Flipbook for Culture and Literacy - Veronika Unun Pratiwi; Farida Nugrahani; Benedictus Sudiyana; Suhailee Sonhuie (Balai Bahasa Provinsi Bali, 2025)
This study aims to explore how four Punakawan characters; Semar, Gareng, Petruk, and Bagong can be utilized through digital Flipbook storytelling to enhance moral knowledge and storytelling skills among elementary school students in Central Java, Indonesia. The objectives are to (1) integrate local cultural values into digital learning media, (2) analyze students’ perceptions of Puna-kawan-themed Flipbooks, and (3) evaluate their effectiveness in improving creativity, ethical understanding, and digital literacy. This study employed a qualitative descriptive method sup-ported by quantitative data. Data were collected through students’ created Flipbooks, reflective journals, observation notes, and teacher interviews. The data were analyzed using content analysis and simple descriptive statistics to identify dominant themes and participation levels. The results showed that students demonstrated higher creativity, stronger moral reasoning, and improved digital literacy. Semar and Petruk were the most preferred characters, while Bagong particularly attracted older students for his critical thinking values. These findings emphasize the pedagogical potential of integrating local wisdom with digital media for character education and 21st-century literacy development. AbstrakPenelitian ini bertujuan untuk mengeksplorasi bagaimana empat tokoh Punakawan; Semar, Gareng, Petruk, dan Bagong, dapat dimanfaatkan melalui penceritaan Flipbook digital untuk meningkatkan pengetahuan moral dan keterampilan mendongeng di kalangan siswa sekolah dasar di Jawa Tengah, Indonesia. Tujuannya adalah untuk (1) mengintegrasikan nilai-nilai budaya lokal ke dalam media pembelajaran digital, (2) menganalisis persepsi siswa terhadap Flipbook bertema Puna-kawan, dan (3) mengevaluasi efektivitasnya dalam meningkatkan kreativitas, pemahaman etika, dan literasi digital. Penelitian ini menggunakan metode deskriptif kualitatif yang didukung oleh data kuantitatif. Data dikumpulkan melalui flipbook yang dibuat siswa, jurnal reflektif, catatan observasi, dan wawancara guru. Data dianalisis menggunakan analisis isi dan statistik deskriptif sederhana untuk mengidentifikasi tema dominan dan tingkat partisipasi. Hasil penelitian menunjukkan bahwa siswa menunjukkan kreativitas yang lebih tinggi, penalaran moral yang lebih kuat, dan peningkatan literasi digital. Semar dan Petruk adalah tokoh yang paling disukai, sementara Bagong khususnya menarik minat siswa yang lebih tua karena nilai-nilai berpikir kritisnya. Temuan ini menekankan potensi pedagogis dari integrasi kearifan lokal dengan media digital untuk pendidikan karakter dan pengembangan literasi abad ke-21.